CLASP Facilitates Transitions between Cortical Microtubule Array Patterns - Thoms, David (Plant Physiol, 2018)
Acentrosomal plant microtubule arrays form patterns at the cell cortex that influence cellular morphogenesis by templating the deposition of cell wall materials, but the molecular basis by which the microtubules form the cortical array patterns remains largely unknown. Loss of the Arabidopsis (Arabidopsis thaliana) microtubule-associated protein, CYTOPLASMIC LINKER ASSOCIATED PROTEIN (AtCLASP), results in cellular growth anisotropy defects in hypocotyl cells. We examined the microtubule array patterning in atclasp-1 null mutants and discovered a significant defect in the timing of transitions between array patterns but no substantive defect in the array patterns per se. Detailed analysis and computational modeling of the microtubule dynamics in two atclasp-1 fluorescent tubulin marker lines revealed marker-dependent effects on depolymerization and catastrophe frequency predicted to alter the steady-state microtubule population. Quantitative in vivo analysis of the underlying microtubule array architecture showed that AtCLASP is required to maintain the number of growing microtubule plus ends during transitions between array patterns. We propose that AtCLASP plays a critical role in cellular morphogenesis through actions on new microtubules that facilitate array transitions.